KEY PRINCIPLES OF GOOD GOVERNANCE WITH PUBLIC FINANCES OF THE LOCAL GOVERNMENT IN THE REPUBLIC OF NORTH MACEDONIA - Zafirova, Angela (University Ss. Cyril and Methodius in Skopje, 2023)
Establishing a transparent, responsible, competing and service-oriented local self-government that is guided in its work according to the principles of good governance is a strategic priority for each country. Good governance is an appropriate, competent management of the municipality's resources, which should provide open access, accountability, transparency, an equal and responsive way of working to meet the needs of citizens. Hence, the main aim of this paper is to define the key principles of good governance of local self-government units in the Republic of North Macedonia, while serving as a basis for future detailed research on the issue. This paper insists to motivate the local self-government units to be more transparent, responsible, accountable and thus take a well-deserved place in the process of reforming local public policies. The legal framework establishes an obligation for local self-government units to apply the key principles of good governance: transparency, accountability, participation and direct communication with citizens. Although good governance as an ideal is very difficult to achieve, it is still necessary to take steps from the local government to bring our municipalities closer to this ideal.